2001
DOI: 10.1068/b2703
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Urban Morphology: The Case of Petah Tikvah

Abstract: Urban evolution is composed of two interlinked phenomena. Over time, changes occur in urban size as measured, for example, by population. The geographic space occupied by human activities and by buildings also changes over time. Those two aspects of urban evolution are linked and, as such, should be studied in tandem. In this paper we present an analysis of the process of formation of urban centers as a result of growth spurts and the structured behavior of individuals. We propose a dynamic model of the spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…However, biological terms were more commonly used in a way not consciously invoking a biological comparison, e.g. "Cities are physical objects that display extreme variety of size and morphology" (Benguigui et al, 2001). Indeed, of the 2371 biological terms identified only 5.44%, 6.28%, and 2.91% were used as analogy, metaphor, or simile, respectively.…”
Section: Biological Comparisonsmentioning
confidence: 99%
“…However, biological terms were more commonly used in a way not consciously invoking a biological comparison, e.g. "Cities are physical objects that display extreme variety of size and morphology" (Benguigui et al, 2001). Indeed, of the 2371 biological terms identified only 5.44%, 6.28%, and 2.91% were used as analogy, metaphor, or simile, respectively.…”
Section: Biological Comparisonsmentioning
confidence: 99%
“…First, not all cities are necessarily fractal. Benguigui et al (2000Benguigui et al ( , 2006 analyzed the fractal dimension of the Tel Aviv metropolitan between 1935 until 2000 and revealed that not every part of the metropolis can be represented, even approximately, by a fractal. Second, and more importantly, spatial patterns at different scales of resolution appear to be similar, despite the fact that the mechanisms that govern the creation of these patterns are different.…”
Section: Fractalsmentioning
confidence: 99%
“…One obvious source of disparity between urban theory and practice is the lack of data that adequately represent urban spatial dynamics. Many researchers have recognized that the use of data delimited on the basis of municipal partitions leads to severe distortions, since their boundaries often are an anachronism and do not signify any actual spatial entities (Anas et al, 1998, Benguigui et al, 2006. This problem becomes especially important when the research follows metropolitan area over time.…”
Section: The Problem Of Urban Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…In between buildings, there are back yards, private and public gardens and lots that are yet to be developed. Studies of urban clusters, defined as continuous built spaces (Benguigui, et al, 2000;2001a;2001b; carried out at a fine spatial resolution, confirm that while open spaces in cities do shrink in quantity, they persist and in the limit represent about a third of the urban land area. More importantly, their connectivity at least in some cities is robust (Czamanski, Malkinson and Toger, 2014;Toger, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%